The lawyer's conscience a history of American lawyer ethics - Ariens, Michael S., 1957- (University Press of Kansas, 2023)
"In 1776, Thomas Paine declared the end of royal rule in America. Instead, "law is king," for the people rule themselves. Paine's declaration is the dominant American understanding of how political power is exercised. In making law king, lawyers became integral to the exercise of political power, so integral to law that one legal ethics philosopher has concluded, "lawyers are the law" in the United States. Lawyers, particularly private practice lawyers, have defended the exercise of this power by arguing they serve the public interest as well as the interests of their paying clients and, lastly, themselves. Since the early twentieth century, lawyers have also pointed to their duty to abide by ethics codes channeling their behavior. In this view, lawyers were in the marketplace selling their services, but not of the marketplace, because the services they provided clients were limited by the oath and the rules of lawyer ethics. Remnants of Conscience is the story of the justifications of the power lawyers have possessed in American history, tracing American lawyer ethics from its origins in the mid-eighteenth century to the crisis of professionalism facing lawyers today"--